SEMIOTICS IN JOHN STEINBECK’S “GRAPE OF WRATH” - masofa, ima (Jurnal Sastra dan Budaya Dinamika, 2017)
This article analyzes signs aspects of Steinbeck’s The Grapes of Wrath by using the Pierce’s concept of semiotics. This article analyzes the semiotic aspects of Steibeck’s The Grapes of Wrath by using the Pierce’s concept of symbolic that is symbol,iconic and index.Symbol in Steinbeck’s the grapes of wrath is road. Iconic in Steinbeck’s the Grapes of Wrath is music. Index in Steinbeck’s the Grapes of Wrath is bank.Keywords: Symbol,Iconic,Index